Dysvascular Transtibial Amputation Due To Artery Stenosis: A Case Report Study - Kurnia Imanawanto; Ditaruni Asrina Utami (Faculty of Medicine, Universitas Airlangga, 2022)
Below-knee (BK) amputation is one of the most commonly performed actions in dysvascular cases, but rare caused by arterial stenosis. Those had significant impacts on clinical functions and affect the contralateral limb, so its need adequate supervision during rehabilitation programs. The report are to describe the stump wound healing of the patient after amputation surgery, stump preparation at pre-prosthetic phase, prevention of knee contracture, prosthetic preparation and use, gait training and evaluation of unaffected limb. A 44-years old female with right below-knee amputation caused by stenosis of right peroneal and dorsalis pedis artery, and the wound in the residual limb was not healed within 4 weeks. She got rehabilitation to accelerate stump healing and stump shaping, maintain knee flexibility, muscle strengthening, cardiovascular endurance, transfer and ambulation. She had good compliance to the programs and achieved independent ambulation using the prosthetic within 6 months. Improvement in residual limb healing within 6 weeks, pain reduction from VAS score 3 to zero, and stump shape changes from buldging to conical. And also in knee joint range of motion, transfer ability, gait pattern using BK prosthetic (by modifying shoe components), and the patient's ability to carry out ADL (BI score 75 to 100). Laser therapy, stump shaping, flexibility exercise, strengthening exercise, endurance exercise, ambulation exercise and prosthetic use on transtibial dysvascular amputation showed good results for ADL. Careful examination to the unaffected limb could identify early occurence of stenosis. Early intervention could prevent future ischaemia and amputation.